ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PAD DI 34 PROVINSI INDONESIA DENGAN MULTILVEL MIXED-EFFECT MODEL - Virgiana Nugransih Siwi; Lia Muntafiah; Lidia Cahya Wuriati (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2021)
Local Own-source Revenue (PAD) optimization is the way how Local Government manages their regional finances as a form of implementing regional autonomy. Therefore, by understanding potential sectors to optimize their PAD, the Local Government will not depend on the Central Government funding, and they can improve their economy. Hence, this study aims to find the determinants of PAD in 34 provinces of Indonesia. This study used multilevel mixed-effect model by using panel data which is the combination of time series data (2015 – 2020) and cross section data (34 provinces). This study found that Labor, Government Spending, Domestic and Foreign Investment, Inflation, and RGDP (Regional Gross Domestic Product) simultaneously affect the PAD. The Labor Force, the Government Spending and RGDP partially had a positive effect on PAD, while the Domestic Investment, the Foreign Investment and Inflation partially did not affect PAD. This study also found that the Labor Force, the Government Spending, and the Inflation had different random effect in every province, while RGDP as the random effect parameter had same random effect in every province.